Caribbean Report 30-01-1998 - Greaves, Keith Stone (anchor); Gordon, Orin (correspondent); May, Steve (correspondent); Lamb, Tom (interviewee); Holder, Jean (interviewee); Perreira, Joseph 'Reds' (interviewee); Fletcher, Raphael (interviewee); Goffe, Leslie (correspondent); Olson, Robert (interviewee); Clare, Irwine (interviewee) (The British Broadcasting Corporation, 1998)
In the wake of the abandoned cricket test match in Sabina Park, Jamaica, scores of cricket fans await refunds on their tickets. British and Caribbean media reactions to the events at Sabina Park are reported. Meanwhile, England and Wales Cricket Board announced that they will be seeking compensation for English fans that traveled to Jamaica for the test. President of Caribbean Tourism Organization, Jean Holder comments on what this incident means for sports tourism in the region. Sports commentator Joseph Reds Pereira calls for more involvement from the West Indies Cricket Board in terms of pitch preparation in the region. CARICOM has announced plans to set up a diplomatic mission in South Africa. Grenada's Foreign Minister Dr. Raphael Fletcher comments on the trade prospects between the countries. A Federal Judge questions whether the US State Department is illegally refusing to issue visas on the basis of skin color. Irwine Clare, a Caribbean immigrant advocate, declares the information confirms what many Caribbean people already suspected.
1. Headlines with Keith Stone Greaves (00:00-00:24)
2. Scores of cricket fans await refunds on their tickets after the abandoned Jamaica test (00:25-01:03)
3. British and Caribbean media deliver their verdict on the pitch at Sabina Park (01:04-04:25)
4. The England and Wales Cricket Board intends to seek compensation for English fans that traveled to Jamaica to view the test (04:26-09:00)
Keywords: Cricket -- West Indies -- Management; Cricket -- West Indies; Cricket grounds -- Jamaica; Cricket -- Tournaments -- England; Rebates -- Jamaica; British newspapers -- Headlines; Mass media and sports -- Caribbean Area; Cricket fans -- England; Sports and tourism -- Caribbean Area; Government missions -- Caribbean Area; Caribbean Area -- Commerce; Diplomatic and consular service; Visas -- United States; Discrimination -- United States; United States -- Emigration and immigration -- Government policy; Admission of nonimmigrants -- United States